Hospitalized elderly: Focus on the humanization of nursing care (Research, Society and Development, 2022)
Introduction: Population aging comprises a growing phenomenon, becoming a challenge for everyone and, in particular, for health services, as it also drives the increase in the prevalence of chronic degenerative diseases and, consequently, the hospitalization of the elderly Objective: To identify nursing care practices aimed at humanization directed to the care of hospitalized elderly. Method: Integrative Review, an Evidence-Based Practice (EBP), in which 93 articles were identified extracted from the databases indexed in the Virtual Health Library (VHL): Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO), Coordination for the Improvement of Higher Education Personnel (Portal CAPES) and Online System of Search and Analysis of Medical Literature (MEDLINE). 10 articles were selected through analytical reading, considering as inclusion criteria the full articles available in full, in Portuguese and published between the years 2017 and 2021, with discussions relevant to the hospitalized elderly. As exclusion criteria, duplicate articles, outside the theme and period defined for this research. Results: Upon reading the articles that make up the corpus of this research, it is observed that, despite being a practice known and developed by many, it is still necessary to carry out new studies that allow approaches based on the opinions of the elderly themselves, not only of professionals, since this is a population that tends to grow even more and, above all, because humanization during care is a practice recommended by law.